CELEBRITY ENNDORSER SISCA KOHL DALAM MENINGKATKAN KEPUTUSAN PEMBELIAN SOSIS KANZLER - Fauzan Noor Qolbi, - (2022)
The development of technology has an impact on social media as a source of information for consumers in making purchasing decisions. This is certainly used by companies to compete to win the market to improve consumer purchasing decisions. Influencer campaigns on social media are one of the promotional media that companies can use to introduce their products/services to consumers. Based on these problems, the authors are interested in examining the effect of celebrity endorser Sisca Kohl in improving the purchasing decision of Kanzler sausage. This research is descriptive verification with a sample of Generation Z students at the Faculty of Economics and Business Education (FPEB) Universitas Pendidikan Indonesia as many as 360 respondents based on the slovin formula who know Sisca Kohl and have bought Kanzler Sausage, using purposive sampling technique and interviewing 10 respondents. To find out the results of the study, the research method was carried out by testing the assumption of normality, correlation analysis, simple regression analysis and hypothesis testing. Hypothesis testing uses t-test to test the hypothesis between the independent variable and the dependent variable. The results showed that there was a positive influence between celebrity endorser Sisca Kohl in increasing the purchasing decision of Kanzler sausage.